Prognostic significance of the wall to lumen ratio of retinal arterioles evaluated by adaptive optics - De Ciuceis, Carolina; Rosei, Claudia Agabiti; Malerba, Paolo; Rossini, Claudia; Nardin, Matteo; Chiarini, Giulia; Famà, Francesca; Lemoli, Matteo; Baresi, Mattia; Petelca, Alina; Bortoluzzi, Chiara; Porteri, Enzo; et al. (European journal of internal medicine, 2024)
•Increased media-to-lumen ratio of subcutaneous small arteries has a prognostic role.•Adaptive optics noninvasively measures the wall-to-lumen ratio of retinal arteriole.•Retinal wall-to-lumen ratio correlates to subcutaneous media-to-lumen ratio.•Patients with total or cardiovascular events show greater wall-to-lumen ratio.•Wall-to-lumen ratio estimation by adaptive optics may predict event free-survival. Microvascular structural alterations may be considered an important form of hypertension-mediated organ damage. An increased media-to-lumen ratio of subcutaneous small arteries evaluated with locally invasive techniques (micromyography) predicts the development of cardiovascular (CV) events. However, it is not known whether retinal arteriole structural alterations evaluated with a noninvasive approach (Adaptive Optics) may have a prognostic significance. Two-hundred and thirty-seven subjects (mean age 58.7 ± 16.1 years, age range 13–89 years; 116 males) were included in the study: 65 normotensive subjects (27.4 %) and 172 patients with essential hypertension or primary aldosteronism (72.6 %). All subjects underwent a non-invasive evaluation of retinal arteriolar wall-to-lumen ratio (WLR) by Adaptive Optics. Subjects were re-evaluated after an average follow-up time of 4.55 years in order to assess the occurrence of clinical events (non CV and/or CV death or events). Fifty-four events occurred in the study population:26 were cardio-cerebrovascular events (ischemic or hemorragic stroke, atrial fibrillation, heart failure, coronary artery disease, peripheral artery disease, cardiac valvular disease) while the remaining were deaths for any cause, or neoplastic diseases. Subjects with events were older and had a WLR of retinal arterioles significantly greater than those without events. The event-free survival was significantly worse in those with a baseline WLR above the median value of the population (0.28) according to Kaplan-Mayer survival curves and multivariate analysis (Cox's proportional hazard model). The evidence was confirmed after restricting the analysis to CV events. Structural alterations of retinal arterioles evaluated by Adaptive Optics may predict total and CV events.